Palaeolithic pioneers : behaviour, abilities, and activity of early homo in European landscapes around the western Mediterranean basin - 1.3-0.05 Ma - Walker, Michael J., (Archaeopress Publishing Ltd, 2017)
Archaic humans were present for over a million years in western Mediterranean Europe where they left very many traces of their early stone-age activities and behaviour, and sometimes even human skeletal remains. This work evaluates archaeological findings about their life-ways at many important sites in Italy, southern France, and Spain, from the earliest ones 1,300,000 years ago, to those of Neanderthals fifty-thousand years ago, just before they were superseded by skeletally-'modern' humans.